2019
DOI: 10.1002/ajoc.201900190
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Controlled Rhodium‐Catalyzed C6‐Selective C−H Alkenylation and Alkylation of 2‐Pyridones with Acrylates

Abstract: A solvent-controlled rhodium-catalyzed C6-selective alkenylation and alkylation of 2-pyridones with acrylates via a pyridine-directed CÀ H cleavage was developed. Using DMF as solvent, the CÀ H alkenylation with acrylates selectively occurs to deliver the corresponding C6-alkenylated 2-pyridones in good yields. On the other hand, the C6-alkylated products are predominantly formed in a more polar and protic solvent, HFIP. Thus, a single set of starting substrates can be divergently transformed to C6-functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Using these starting materials, several literature precedents have described chemodivergent reactivity depending on the reaction conditions: hydroarylation vs. oxidative annulation (Scheme 2b). 7,8 These reactivity patterns represented an ideal test case for investigating the role of HFIP since, a priori, it could play opposite effects. In both cases, the authors discovered that the addition of HFIP enables the use of milder conditions for obtaining the corresponding product in almost quantitative yields, but presumably due to different reasons.…”
Section: Hfip and Tfe: Super Polar Super H-bond Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these starting materials, several literature precedents have described chemodivergent reactivity depending on the reaction conditions: hydroarylation vs. oxidative annulation (Scheme 2b). 7,8 These reactivity patterns represented an ideal test case for investigating the role of HFIP since, a priori, it could play opposite effects. In both cases, the authors discovered that the addition of HFIP enables the use of milder conditions for obtaining the corresponding product in almost quantitative yields, but presumably due to different reasons.…”
Section: Hfip and Tfe: Super Polar Super H-bond Donorsmentioning
confidence: 99%
“…Miura and co-workers have demonstrated the selective C-H alkenylation and alkylation of 2-pyridones with acrylates, depending on the employed solvent (Scheme 3a). 7 Using DMF, the authors observed the expected formation of the C6-alkenylated product. In sharp contrast, HFIP promoted the alkylation processes due to its capability to act as a proton source.…”
Section: Hfip and Tfe: Super Polar Super H-bond Donorsmentioning
confidence: 99%
“…Among the large number of aza-heterocycles available, pyridones and quinolones, both of which have a common six-membered aza-framework, exhibit a wide range of pharmacologically important activities ( Figure 1) [6][7][8][9][10]. Therefore, various methods for the preparation of structurally diverse pyridones and quinolones have been studied in detail [6,[11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Among the large number of aza-heterocycles available, pyridones and quinolones, both of which have a common six-membered aza-framework, exhibit a wide range of pharmacologically important activities ( Figure 1) [6][7][8][9][10]. Therefore, various methods for the preparation of structurally diverse pyridones and quinolones have been studied in detail [6,[11][12][13][14][15][16][17][18][19][20][21]. Conventional strategies for the synthesis of aza-heterocycles involve (1) construction of azaheterocycle frameworks from prefunctionalized starting materials, (2) ring transformation leading to Conventional strategies for the synthesis of aza-heterocycles involve (1) construction of aza-heterocycle frameworks from prefunctionalized starting materials, (2) ring transformation leading to aza-heterocycle frameworks, and (3) direct functionalization of aza-heterocycle frameworks, which are supplementary to each other ( Figure 2) [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation